Determinan Partisipasi Pembudidaya dalam Pengembangan Kelompok Ternak Lebah Trigona di Kabupaten Belitung Timur: Determinants of Farmers’ Participation in the Development of Trigona Beekeeping Groups in East Belitung Regency - Guspian, Ipan; Saleh, Amiruddin; Matindas, Krishnarini (Journal of Integrated Agribusiness, 2025)
This study examines the determinants of cultivators’ participation in the development of Trigona sp. beekeeping groups in East Belitung Regency. A deductive approach was employed using quantitative descriptive analysis. The research was conducted in East Belitung Regency, Bangka Belitung Islands Province, focusing on Trigona sp. beekeepers who are members of the East Belitung Teran Honey Geographical Indication Protection Society (MPIG). Sampling was conducted through a probability sampling technique, specifically simple random sampling, yielding 135 respondents. Data were collected through surveys using structured questionnaires and interviews with Trigona sp. beekeepers. Data analysis was performed using Microsoft Excel and SPSS software, applying multiple linear regression. The findings indicate that the determinants influencing cultivators’ participation in developing Trigona sp. beekeeping groups in East Belitung Regency, both individually and collectively, include individual characteristics, credibility of information sources, information quality, communication channels, and communication context.